Mutual effects of humic acid content and nitrogen sources for vegetative development and flowering of snapdragon (Antirrhinum majus L.) - Nurdilek Gulmezoglu; Cigdem Yücel; Sibel Yigiter-Saricam (Acta Scientiarum Polonorum: Hortorum Cultus, 2024)
Snapdragon (Antirrhinum majus L.), a garden plant cherished for its unique and colorful flowers, is widely used in bouquets and wreaths as a cut flower. The purpose of this study is to examine the effects of nitrogen sources (ammonium sulfate, AS; ammonium nitrate, AN; and urea) and humic acids from lignite sources (TKI-Humas and HUM-Zn) on the growth and flower production of snapdragon that are grown in pots under controlled conditions. It has been observed that plants started to flower during applications of HUM-Zn with AN and urea, whereas they remained at the vegetative stage during the application of HUM-Zn with AS. Furthermore, it has been determined that the two humic acid sources with AS usage prolonged the vegetative development and did not induce flowering of plants. Simultaneous application of humic acid and nitrogen sources has caused an increase in the leaf width, peduncle diameter, floret weight, chlorophyll content, and biomass of the snapdragon. Results show that the application of HUM-Zn with AN and urea has been effective on the plant’s vegetative organs, flowering, and dry weight. It indicated that HUM-Zn contains zinc, which is effective in flowering and biomass development. In conclusion, it was concluded that the simultaneous application of humic acid with AN or urea rapidly affected the flowering process of snapdragon.